“This is a theory of monads…”. Sketching the similarities between Leibniz’s monads and Whitehead’s actual entities - Raffo Quintana, Federico (Logos. Anales del Seminario de Metafísica, 2025)
The article explores certain similarities between Leibniz’s theory of monads and Whitehead’s philosophy of organism. Starting from Whitehead’s claim that his proposal constitutes “a theory of monads”, five key aspects are examined: the homogeneous character of ultimate realities, their relational nature, the priority of perception over apperception (in Leibniz) or of experience over consciousness (in Whitehead), the generality of perception or prehension, and the use of the notion of appetition in relation to final causality. The proposed similarities, however, are far from implying full agreement between their respective conceptions. In this regard, some points of divergence are also highlighted. Thus, it is argued that although the philosophies of Leibniz and Whitehead share a certain common structure, there are significant differences between them.
Keywords: Leibniz; Whitehead; metaphysics; monad; experience; appetition; philosophy of organism; relationality; perception; prehension